Forming of the productivity and quality of grain corn hybrid depending on predecessor - Баган, А. В. (Scientific Progress & Innovations, 2015)
The elements of the productivity, level of the productivity and indexes of quality of grain of corn hybrids of LTD «Monsanto» depending on a predecessor in the production terms of Poltava area are researched. Influence of winter wheat and pea on forming of head mass, grain mass from a stalk, productivity index, 1000 grains mass and albumen maintenance at the researched hybrids is studied. The best predecessor was selected. It is a pea. The best hybrids of corn (after economic-valuable signs) are made to order for growing.